2019
DOI: 10.3390/app9101976
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Nanofluids for the Thermal Enhancement in Radiative and Dissipative Flow over a Wedge

Abstract: The colloidal analysis for H2O and EG (Ethylene Glycol) by considering the influence of radiative heat flux and viscous dissipation is not performed so far. This study is performed to fill up this gap. Therefore, the flow of water and ethylene glycol functionalized magnetite nanoparticles over a moving wedge is examined. For thermal enhancement, two different magnetite nanoparticles, namely CoFe 2 O 4 (Cobalt ferrite) and Mn − ZnFe 2 O 4 ( Mn − Zn ferrite), diluted in the bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…However, numerical schemes are reliable and efficient for such models. Thus, a numerical scheme along with the coupling of shooting techniques ( Ahmed et al, 2019 ; Khan et al, 2021 ) implemented. Primarily, this technique is based on the reduction of a higher-order nonlinear model into a system of first-order via some sort of transformation.…”
Section: Mathematical Analysis Of Mwcnts-pg Modelmentioning
confidence: 99%
“…However, numerical schemes are reliable and efficient for such models. Thus, a numerical scheme along with the coupling of shooting techniques ( Ahmed et al, 2019 ; Khan et al, 2021 ) implemented. Primarily, this technique is based on the reduction of a higher-order nonlinear model into a system of first-order via some sort of transformation.…”
Section: Mathematical Analysis Of Mwcnts-pg Modelmentioning
confidence: 99%
“…Keeping these assumptions in mind, and with the reference from Mallikarjuna et al (2016) and Ahmed et al (2019), the mathematical model are formulated as…”
Section: Fig 1 Model Illustration With Coordinate Systemmentioning
confidence: 99%
“…The subscript of f and s refer to the base liquid and MNP, separately. The thermal and physical characteristics for base liquid and MNP are given in Table 2 (Ahmed et al, 2019;Raju & Sandeep, 2017;Gul et al, 2015), where  is the MNP volume fraction and…”
Section: Fig 1 Model Illustration With Coordinate Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the single‐phase nanofluid model, Jusoh et al 23 observed three types of base fluids: water false(Pr=6.2false) $({\Pr }=6.2)$, kerosene false(Pr=21false) $({\Pr }=21)$, and methanol false(Pr=7.38false) $({\Pr }=7.38)$ and they concluded that the ferrofluid with the highest Prandtl number has the maximum heat transfer rate and thermal conductivity. The MNFs flow towards a wedge utilizing cobalt ferrite–water (CoFe 2 O 4 –H 2 O) and manganese–zinc ferrite–water (Mn–ZnFe 2 O 4 –H 2 O) nanofluids was studied by Ahmed et al 27 Hayat et al 28 analyzed the three‐dimensional magnetite nanofluid flow over a nonlinearly stretching sheet with homogeneous–heterogeneous reactions. Mohamed et al 29 studied the impact of Newtonian heating and slip effect on magnetohydrodynamics (MHD) stagnation point flow of a magnetite‐water nanofluid towards a stretching sheet.…”
Section: Introductionmentioning
confidence: 99%